2021
DOI: 10.21037/tlcr-20-1179
|View full text |Cite
|
Sign up to set email alerts
|

The person behind the nodule: a narrative review of the psychological impact of lung cancer screening

Abstract: Lung cancer is the leading cause of cancer mortality globally, responsible for an estimated 1.76 million deaths worldwide in 2018 alone. Screening adults at high risk of lung cancer using low-dose computed tomography (LDCT) significantly reduces lung cancer mortality by finding the disease at an early, treatable stage. Many countries are actively considering whether to implement screening for their highrisk populations in light of the recently published Dutch-Belgian trial 'NELSON'. In deciding whether to impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The NLST, NELSON and the Pan-Canadian Early Detection of Lung Cancer Study (PAN-CAN) trials found no evidence of clinically adverse psychological impacts on generic health-related quality of life measures overall at short- or long-term follow-up for screened cohorts. 30 Scores of anxiety and depression have been shown to differ by LDCT result with increased scores for those receiving indeterminate and suspicious results. However, these have been short-lived.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…The NLST, NELSON and the Pan-Canadian Early Detection of Lung Cancer Study (PAN-CAN) trials found no evidence of clinically adverse psychological impacts on generic health-related quality of life measures overall at short- or long-term follow-up for screened cohorts. 30 Scores of anxiety and depression have been shown to differ by LDCT result with increased scores for those receiving indeterminate and suspicious results. However, these have been short-lived.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…Several studies have also shown that the fear of cancer and psychological distress of participants who received uncertain nodules or abnormal screening results increased obviously in a short-term period, but the difference may be not clinically significant ( 7 , 11 , 32 ). In Contrast, several studies have pointed out that the diagnosis of pulmonary nodules by lung cancer screening does not seem to lead to adverse psychological harm ( 18 , 33 ); (b) Breast cancer screening: 70% of participants with positive screening results of breast cancer suffered from severe psychological distress and increased anxiety and depression, especially for patients whose screening results need further examination. No psychological impact was found in those who received negative screening results ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the psychological impact of cancer screening are inconsistent. Current research in this field mainly focuses on the following types of cancer: lung cancer, breast cancer, colorectal cancer, cervical cancer and ovarian cancer ( 7 , 16 – 18 ). However, research on the psychological impact caused by EC screening is still limited and unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial studies have been carried out to investigate the psychological burden in lung cancer screening recipients (4,7,8). Indeterminate or suspicious screening results were usually followed by a short-term increase of psychological burden to a clinically significant level (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Various instruments were used to measure the psychological state among recipients of lung cancer screening, including the European Quality of Life (EQ-5D), the State-Trait Anxiety Inventory (STAI), the impact of event scale (IES), consequences of screening in Lung Cancer (COS-LC), as well as the Hospital Anxiety and Depression Scale (HADS) (4,7,8). Except for HADS, most of these scales are generic HRQoL measures which include dimensions of psychological outcomes.…”
Section: Introductionmentioning
confidence: 99%